Photothermal effects of CuS-BSA nanoparticles on H22 hepatoma-bearing mice - Dun, Xinyu; Liu, Shuliang; Ge, Nan; Liu, Meng; Li, Ming; Zhang, Jun; Bao, Hongxu; Li, Benying; Zhang, Hua; Cui, Lianhua (Frontiers in Pharmacology, 2022)
Abstract The objective of this study was to evaluate the in vivo application and photothermal ablation effects and mechanism of copper sulfide nanoparticles (CuS NPs) in hepatocellular carcinoma (HCC). Sheet-like CuS-BSA NPs with a particle size of 30 nm were synthesized using bovine serum albumin (BSA) as a biological modifier, and were physically characterized. To provide a reference range for the biosafety dose of CuS-BSA NPs, 36 male Kunming mice were randomly assigned into six groups. Different one-time doses of CuS-BSA NPs were injected via tail vein injection, and the potential damages of liver, kidney and spleen were observed 14 days later. To evaluate the in vivo photothermal effect of CuS-BSA NPs, male Kunming mice were used to establish the H22 hepatoma-bearing mouse model and were randomly assigned into six groups. CuS-BSA NPs (600 μg/kg) were injected via tail vein or intratumoral injection. Irradiations were performed 30 min after injection, with a 980 nm near-infrared laser (2.0 W/cm2) for 10 min once a week for 3 weeks. The results indicated that the CuS-BSA NPs had good dispersibility in three different solvents and had a strong absorption peak at 980 nm. The heating curves demonstrated that the photothermal effects of CuS-BSA NPs aqueous solution exhibited concentration dependence and power density dependence. In the in vivo experiment, when the doses of CuS-BSA NPs were in the range of 1800-7200 μg/kg, the thymus index and spleen index of mice were not significantly different from those of the control group, and the structures of liver, kidney and spleen were intact without remarkable pathological changes. A lower dose of CuS-BSA NPs (600 μg/kg) could effectively inhibit tumor growth in H22 hepatoma-bearing mice at 980 nm NIR. Moreover, under the near-infrared laser irradiation, both in the tail vein injection group and the intratumoral injection group, a large area of necrosis in the tumor tissue, as well as the up-regulation of apoptotic proteins including cleaved caspase-3 and cleaved caspase-9 were observed. CuS-BSA NPs are promising photothermal agents in the photothermal therapy of cancer.